Antibacterial And Antibiofilm Activities Of Ethyl Acetate Extract Of Nigrospora Sphaerica Cl-Op30 Isolated From Swietenia Macrophylla Leaf - Ahmad Mokhtar, Nur A’fina (2019)
This research was aimed to study antibacterial and antibiofilm activities of an endophytic fungus Nigrospora sphaerica CL-OP30 isolated from Swietenia macrophylla plant. Quantitative measurement of antibacterial activity revealed that this endophyte produced the highest antibacterial activity at day 12 of cultivation.